Languages and children-making the match: new languages for young learners - Curtain, Helena; Dahlberg, Carol Ann
With a focus on communicative language teaching as it reflects cognitive and second language acquisition theory, this classic in the field provides a wealth of strategies and activities ready to use in the K-8 classrom.